Cerebral and cerebellar MRI volumes in Williams syndrome - Osório, A (2016)
Individuals with Williams syndrome (WS) present a set of cognitive, affective and motor symptoms that resemble those of patients with lesions to the cerebellum. Although there is some evidence for overall structural alterations in this brain region in WS, explorations on cerebellar white matter and cerebellar cortex volumes remain rather neglected. We aimed to compare absolute and relative cerebellar volumes, as well as patterns of white matter to cortex volumes in this brain region, between a group of individuals with WS and a group of healthy controls. T1-weighted magnetic resonance images were acquired in 17 individuals with WS and in 15 typically developing individuals. Our results showed that even though individuals from the clinical group had significantly smaller cerebrums (and cerebellums), cerebellar volumes relative to intracranial volumes were significantly enlarged. In addition, while gray matter was relatively spared and white matter disproportionately reduced in the cerebrum in WS, relative cerebellar cortex and white matter volumes were preserved. These findings support the hypothesis that volume alterations in the cerebellum are associated with the cognitive, affective and motor profiles in WS.